Quiero resolver ∫6−6(4e2x+2)2e2xdx∫6−6(4e2x+2)2e2xdx pero me malos resultados:
∫6−6(4e2x+2)2e2xdx=∫6−616e4x+16e2x+4e2xdx∫6−6(4e2x+2)2e2xdx=∫6−616e4x+16e2x+4e2xdx
=[(4e4x+8e2x+4x)2e2x]6−6=[8e4x+16e2x+8xe2x]6−6=[(4e4x+8e2x+4x)2e2x]6−6=[8e4x+16e2x+8xe2x]6−6
=(8e24+16e12+48e12)−(8e−24+16e−12−48e−12)=(8e24+16e12+48e12)−(8e−24+16e−12−48e−12)
=e−12(8e24+16e12+48)−e12(8e−24+16e−12−48)=e−12(8e24+16e12+48)−e12(8e−24+16e−12−48)
=8e12+16+48e−12−(8e−12+16−48e12)=8e12+16+48e−12−(8e−12+16−48e12)
=8e12+16+48e−12−8e−12−16+48e12)=8e12+16+48e−12−8e−12−16+48e12)
=56e12+56e−12=56e12+56e−12
A donde voy mal?